2001
DOI: 10.1046/j.1460-9592.2001.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative considerations in a hypothyroid infant with hepatic haemangioma

Abstract: Hepatic haemangiomas in infants are rare. An infant with both a hepatic haemangioma and a severe hypothyroid condition, unresponsive to conventional thyroxine therapy, will be described. This case presented here is the perioperative management of a critically ill infant who had myocardial depression secondary to hypothyroidism and a hepatic haemangioma that required embolization. To our knowledge, this is the first published report describing intravenous triiodothyronine as a therapeutic modality to stabilize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…3,11 In some of the previous cases, children required extremely high doses of T4, T3 or combined thyroid replacement therapy. 4,12,13 Doses ranging between 5 and 94 mg/kg/d have been reported. 8 (For comparison, in conventional hypothyroidism the thyroid replacement therapy dose that maintains euthyroid status in infants ranges from 5 to 10 mg/kg/d.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,11 In some of the previous cases, children required extremely high doses of T4, T3 or combined thyroid replacement therapy. 4,12,13 Doses ranging between 5 and 94 mg/kg/d have been reported. 8 (For comparison, in conventional hypothyroidism the thyroid replacement therapy dose that maintains euthyroid status in infants ranges from 5 to 10 mg/kg/d.)…”
Section: Discussionmentioning
confidence: 99%
“…11,12 This suggests that a search for HHE should be undertaken in infants with severe unexplained hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on this type of consumptive hypothyroidism report the use of levothyroxine or levothyroxine plus liothyronine for treatment [1][2][3][4][5][6][7][8][9][10][11][12]14]; while 1 study reported the use of liothyronine plus prednisolone [13]. However, there is no report of using liothyronine plus propranolol for the treatment of consumptive hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…KH'de konjenital kalp hastalıklarının yüksek prevalansta gö-rülmesi nedeniyle bu hastalara rutin ekokardiyografi uygulanması gerektiği bildirilmektedir (4) . Ayrıca tiroid hormonunun aktif formu olan triiyodotironinin spesifik olarak miyokarda etki ettiği ve hem direkt hem de indirekt olarak kardiyak fonksiyonu etkilediği gösteril-miştir (5,6) . Bu literatür bilgileri doğrultusunda hastamı-za preoperatif ekokardiyografi uygulanmış ve herhangi bir kardiyak anomaliye rastlanmamıştır.…”
Section: Discussionunclassified